2022
DOI: 10.1186/s12903-022-02408-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concentrated growth factor (CGF) on postoperative sequel of completely impacted lower third molar extraction: a randomized controlled clinical study

Abstract: Background The surgical extraction of impacted third molars is one of the most common procedures in oral and maxillofacial surgery, which associated with several postoperative complications. The aim of this clinical trial was to estimate the implication of concentrated growth factor (CGF) on postoperative sequelae after the completely impacted lower third molar extraction. Materials and methods A total of 74 sides of 37 participants who had complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 39 publications
1
22
1
Order By: Relevance
“…Fang et al [22] showed that the lling of CGF gel in tooth extraction can signi cantly reduce the pain response of patients 2h, 24h and 48h after surgery. Elayah et al [23] also showed that CGF could signi cantly reduce the pain response caused by tooth extraction at 3 and 7 days after surgery. This may be related to the following aspects that CGF is a brous protein structure which acts as a scaffold material and reservoir to transfer growth factors and help accelerate the healing stage [24].…”
Section: Discussionmentioning
confidence: 96%
“…Fang et al [22] showed that the lling of CGF gel in tooth extraction can signi cantly reduce the pain response of patients 2h, 24h and 48h after surgery. Elayah et al [23] also showed that CGF could signi cantly reduce the pain response caused by tooth extraction at 3 and 7 days after surgery. This may be related to the following aspects that CGF is a brous protein structure which acts as a scaffold material and reservoir to transfer growth factors and help accelerate the healing stage [24].…”
Section: Discussionmentioning
confidence: 96%
“…These mixed results from clinical trials have hindered the application of growth factors. CGF, obtained from a patient's autologous venous blood, is characterized by rich growth factors and fibrin, which have concert effect in treatment thus leading to beneficial outcomes [14,35].…”
Section: Discussionmentioning
confidence: 99%
“…CGF is obtained by centrifuging blood samples at varying speeds using a special centrifuge device (Medifuge, Silfradentsrl, Italy). This technique, with its different and controlled centrifuge speeds, allows for the production of a much larger and denser brin matrix with abundant growth factors [19][20][21]. Additionally, studies have found the presence of CD34 + stem cells, which play an important role in angiogenesis, in PRF concentrates.…”
Section: Introductionmentioning
confidence: 99%